The evident connexion Hume on personal identity - Strawson, Galen (Oxford : Oxford University Press, 2011)
'The Evident Connexion' presents a bold new reading of David Hume's famous 'bundle' theory of the self or mind, and his later rejection of it. Galen Strawson illuminates the 'uniting principle' of Hume's philosophy and argues that the bundle theory does not, as widely supposed, claim that there are no subjects of experience.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hume, David, -- 1711-1776.; Self (Philosophy); Identity (Philosophical concept)